How to write a better thesis - Evans, D.G. (David G.); Gruba, Paul (Carlton South, Vic : Melbourne University Press, 2002)
Second edition of the best selling guide to thesis writing: revised, updated and more useful than ever.
Contents : Introduction -- What's a thesis? -- Making a strong start -- Making your word processor work for you -- The introductory chapter -- The background chapters -- The chapter on design of your own work -- The results chapters -- The discussion or evaluation -- The conclusions -- Before you finally submit -- Disseminating your work.
Includes index.
Includes bibliographical references and index.
Tertiary students.
Keywords: Report writing; Dissertations, Academic